Analisis Pengaruh Kualitas Layanan Terhadap Kepuasan Pelanggan Toserba Yogya di Bandung - Agisni Alawiyah; Halimah Zahrah; Annisa Desfia; Karmelia Ravensky (PENG: Jurnal Ekonomi dan Manajemen, 2025)
The development of the modern retail industry has made service quality a key benchmark for retaining customers and differentiating retailers. Toserba Yogya Heritage, as a player in this sector, is expected to improve service quality to meet customer expectations. This study aims to analyze service quality, customer satisfaction, service ethics, and consumer protection at Toserba Yogya. A qualitative approach was used, involving interviews and questionnaires. The results show that Toserba Yogya’s services are generally satisfactory. Employees serve customers professionally and with a humanistic approach. Customer satisfaction remains high, ethical service practices are consistently applied, and consumer protection follows relevant regulations. These aspects are reflected in the customers’ experience of satisfaction, transparency, and prompt service. However, minor issues remain, such as frequent changes in product layout, which can affect convenience. The study concludes that Toserba Yogya should maintain its service quality and provide regular staff training to enhance customer satisfaction and foster loyalty.